Alleviating Food Insecurity in Asia. Issue 2 (1st September 2014) - Warr, Peter
Abstract : Despite recent progress, Asia has many more food insecure people than the rest of the world combined. The prevalence of stunting and underweight in children far exceeds the global average. Expansion of agricultural output within Asian countries themselves is strongly associated with reductions in the rate of undernourishment. It is not sufficient to rely solely on aggregate economic growth or reductions in poverty incidence to reduce food insecurity. But higher food prices increase the rate of undernourishment. The policy imperative is to raise agricultural output without at the same time raising food prices. Investment in the infrastructure and knowledge required to raise agricultural productivity achieves that objective. Agricultural protection does not, because the number of food insecure people who are net sellers of food is exceeded by the number who are net purchasers of food and for whom increased food prices mean greater food insecurity.